Customer Lived Experiences in Islamic Home Financing: Towards a Maqashid-al-Shariah-Oriented Financing Model - Anas Tania Januari; Muhtadi Ridwan; Ahmad Djalaluddin (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
This study explores the lived experiences of customers utilizing Islamic home financing in Malang City, Indonesia, focusing on how they perceive the practice beyond its financial transactions. While Indonesia's Islamic banking sector continues to expand, limited research examines how customers internalize ethical and spiritual values within financing schemes such as murābaḥah and mushārakah mutanāqiṣah. Using Husserl's descriptive phenomenology, in-depth interviews were conducted with clients of Islamic banks in Malang. The analysis revealed four key themes: (1) religious, economic, and practical motivations influencing financing decisions; (2) the conceptualization of home ownership as a symbol of dignity, familial trust, and intergenerational security; (3) experiences of financial challenges and adaptive strategies for fulfilling obligations; and (4) spiritual meanings of home financing as a path to divine blessing (barakah) and worship. These findings demonstrate that Islamic home financing functions not merely as a financial instrument but also as a multidimensional lived experience that integrates material and spiritual aspirations. Theoretically, this research enriches Islamic finance literature through phenomenological insights, while practically offering implications for Islamic financial institutions and regulators to strengthen ethical service delivery, product innovation, and consumer literacy aligned with the maqāṣid al-sharī‘ah framework.